Potential of temperate agroforestry systems to deliver ecosystem services: An evidence map - Andrea Schievano; Camille Rubeaud; Margret Köthke; Beatrice Landoni; Damien Beillouin; Marta Pérez-Soba; Simona Bosco; Rui Catarino; Giovanni Tamburini; David Makowski; Sonja Kay (Ecosystem Services, 2026)

Cooperative extension’s public service mission and the challenge of climate change - David Kay; Paul Lachapelle (Climatic Change, 2026)

A Digital Twin Ocean: can we improve coastal ocean forecasts using targeted marine autonomy? - Dale Partridge; Deep Banerjee; David Ford; Ke Wang; Jozef Skákala; Juliane Wihsgott; Prathyush P. Menon; Susan Kay; Daniel Clewley; Andrea Rochner; Emma Sullivan; Matthew Palmer (Ocean Science, 2026)
This study outlines the development and testing of a Digital Twin Ocean (DTO) framework, aimed at improving coastal ocean forecasts through the use of autonomous underwater gliders. A fleet of gliders were deployed in the western English Channel during August-September 2024 to collect measurements of temperature, salinity, chlorophyll and oxygen, aiming to track the movement of the harmful algal bloom Karenia mikimotoi. Measurements were assimilated into a very high resolution (1.5 km) numerical forecast model, with an implementation of biogeochemistry data assimilation for this purpose. The model forecast was then used by a probabilistic uncertainty model to plan a series of waypoints to navigate the glider fleet towards features of interest. By utilising a continuous feedback loop of measurement, prediction, guidance, and refinement a system with real time coupling between the real ocean environment and its digital counterpart has been established. Building upon a prior pilot study of Ford et al. (2022), this work improves every element of the system to address several limitations of the prior configuration. Whilst a bloom was present in the wider area, measurements and modeling suggest it didn't enter the glider operation zone. Despite this and other operational challenges the mission clearly demonstrates the benefits of such a system. The ability to simultaneously track multiple features of interest, namely chlorophyll maxima and oxygen minima, would not have been possible with a single glider resulting in significant benefits to the system. Furthermore, the improvement to biogeochemical forecasting has been demonstrated through a series of post mission experiments, highlighting the advantages of high temporal resolution observations and increased spatial resolution of the model.

The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

Within-session dose–response and between-session carry-over effects of eccentric contractions versus static stretches on range of motion and muscle–tendon mechanics - Anthony David Kay; Anthony William Baross; Brett Anthony Baxter; Anthony John Blazevich (European Journal of Applied Physiology, 2026)
Purpose Eccentric resistance training produces substantial increases in maximum joint range of motion (ROM), highlighting its potential as an alternative to static stretching. However, little is known about the short-term effects or associated mechanisms. Therefore, this study compared within-session responses and between-session carry-over effects of eccentric contractions and static stretching in 18 healthy human volunteers. Methods Using a counterbalanced crossover design, participants completed four sessions across two conditions: Eccentric contractions (EC 1 , EC 2 ) and static stretching (SS 1 , SS 2 ), with 48–72 h between sessions. EC comprised 5 sets of 10 × 3-s isokinetic eccentric contractions while SS comprised 5 sets of 30-s static stretches (total time under tension = 150 s). Dorsiflexion ROM and passive plantarflexor torque were recorded before and after each set, and maximal isometric plantarflexor torque, active Achilles tendon stiffness, and passive gastrocnemius medialis stiffness were measured pre- and post-intervention. Results Significant within-session increases in ROM (2.2°–6.0°) and reductions in muscle–tendon unit (MTU) stiffness (2.7–7.3%) and muscle stiffness (8.4%) occurred after both EC 1 and SS 1 . However, only EC 1 improved stretch tolerance (30.7%) and decreased Achilles tendon stiffness (12.0%). Comparable between-session carry-over effects occurred after two sessions of stretches and contractions in pre-intervention ROM (5.9°, collapsed data), stretch tolerance (38.0%), and MTU stiffness (41.7%). Conclusion Eccentric contractions produced more than twice the acute ROM increase and greater changes in stiffness and stretch tolerance than static stretching. The significant carry-over effects after two sessions also indicate a more potent stimulus for increasing ROM, with important implications for clinical practice and exercise prescription.

Verification of the medicinal value of Patriniae Herba for colon cancer using preclinical models - Huihai Yang; Grace Gar-Lee Yue; Tao Zheng; Kwan-Ho Wong; Dandan Hu; Man-Ho Tong; David Tai-Wai Lau; Hung Kay Lee; Pang-Chiu Shaw; Clara Bik-San Lau (Phytochemistry Letters, 2025)

Retrofitted watershed scale green infrastructure reduces heavy metals in urban stormwater from residential land use - Joseph S. Smith; Kay Bernard; Kathryn M. Boening-Ulman; Jay F. Martin; R. Andrew Tirpak; David M. Wituszynski; Ryan J. Winston (Journal of Hazardous Materials, 2025)

Large cobblestone dams for natural flood management in wide peatland gullies - Adam Ryan Johnston; David Brown; Tim Allott; Salim Goudarzi; Martin Kay; David Milledge; Emma Shuttleworth; Tom Spencer; Martin Evans (Ecological Engineering, 2025)

Marine data assimilation in the UK: the past, the present, and the vision for the future - Jozef Skákala; David Ford; Keith Haines; Amos Lawless; Matthew J. Martin; Philip Browne; Marcin Chrust; Stefano Ciavatta; Alison Fowler; Daniel Lea; Matthew Palmer; Andrea Rochner; et al. (Ocean Science, 2025)
In the last 2 decades, UK research institutes have led a wide range of developments in marine data assimilation (MDA), covering areas from operational applications in physics and biogeochemistry to fundamental theory. We highlight the emergence of strong collaboration in the UK MDA community over this period and the increasing unification of its tools. We focus on identifying the MDA stakeholder community and current/future areas of impact, as well as current trends and future opportunities. This includes the rapid growth of machine learning (ML)/artificial intelligence (AI) and digital-twin applications. We articulate a vision for the future, including the need for future types of observational data (whether planned missions or hypothetical) and how the community should respond to increases in computational power and new computer architectures (e.g. exascale computing). We contrast the requirements of different MDA areas, including physics, biogeochemistry, and coupled data assimilation (DA). Although the specifics of the vision depend on each area, common themes emerge. We advocate for balanced redistribution of new computational capability among increased model resolution, model complexity, more sophisticated DA algorithms, and uncertainty representation (e.g. ensembles). We also advocate for integrated approaches, such as strongly coupled DA (ocean–atmosphere, physics–biogeochemistry, and ocean–sea ice) and the use of ML/AI components (e.g. for multivariate increment balancing, bias correction, model emulation, observation re-gridding, or fusion).

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Might I have to move due to climate change? The role of exposure to risk and political partisanship in anticipation of future relocation - Lindy Williams; David Kay (Climatic Change, 2024)
Recently, the body of research that assesses belief in climate change has grown, as has the number of studies appraising how experience with the impacts of climate change might affect public opinion. However, less research has addressed the question of whether/how people believe climate change will manifest itself in their own lives, or how it might affect behavioral responses more generally. Using two rounds of national survey data from 2016 and 2020, we examine the associations between climate risk, political party affiliation, and one potential planned adaptation behavior, relocation. Our results suggest that both exposure to risk and political identification help shape respondents’ beliefs. Several measures of risk are associated with respondents’ reports that weather/climate might cause them to move in the future and there is evidence to suggest that their awareness of risk may have increased between the two surveys. Regarding political affiliation, we find in one set of analyses that Republicans interviewed in 2020 were less likely than other political subgroups, including Republicans interviewed in 2016, to say weather/climate could have a potentially strong influence on future relocation decisions. We also find strong effects of age in one set of analyses, where younger respondents were much more likely than those at middle or older ages to report that weather/climate could exert a strong to moderate influence on a future move.

Integrated analysis of ammonium origins in a Serbian anoxic alluvial aquifer: Insight from physicochemical, isotopic, microbiological data - Marija Perović; Vesna Obradović; Vesna Zuber-Radenković; David Mitrinović; Kay Knoeller; Maja Turk Sekulić (Applied Geochemistry, 2024)

Lower crustal control in the iron isotope systematics of plutonic xenoliths from Adak Island, Central Aleutians, with implications for arc magma geochemistry - Emma S. Sosa; Claire E. Bucholz; Juan David Hernández-Montenegro; Michael A. Kipp; François L.H. Tissot; Barbara C. Ratschbacher; Jennifer M. Jackson; Suzanne Mahlburg Kay; Robert W. Kay (Geochimica et Cosmochimica Acta, 2024)

A multispecies hierarchical model to integrate count and distance‐sampling data - Neil A. Gilbert; Caroline M. Blommel; Matthew T. Farr; David S. Green; Kay E. Holekamp; Elise F. Zipkin (Ecology, 2024)
Integrated community models—an emerging framework in which multiple data sources for multiple species are analyzed simultaneously—offer opportunities to expand inferences beyond the single‐species and single‐data‐source approaches common in ecology. We developed a novel integrated community model that combines distance sampling and single‐visit count data; within the model, information is shared among data sources (via a joint likelihood) and species (via a random‐effects structure) to estimate abundance patterns across a community. Parameters relating to abundance are shared between data sources, and the model can specify either shared or separate observation processes for each data source. Simulations demonstrated that the model provided unbiased estimates of abundance and detection parameters even when detection probabilities varied between the data types. The integrated community model also provided more accurate and more precise parameter estimates than alternative single‐species and single‐data‐source models in many instances. We applied the model to a community of 11 herbivore species in the Masai Mara National Reserve, Kenya, and found considerable interspecific variation in response to local wildlife management practices: Five species showed higher abundances in a region with passive conservation enforcement (median across species: 4.5× higher), three species showed higher abundances in a region with active conservation enforcement (median: 3.9× higher), and the remaining three species showed no abundance differences between the two regions. Furthermore, the community average of abundance was slightly higher in the region with active conservation enforcement but not definitively so (posterior mean: higher by 0.20 animals; 95% credible interval: 1.43 fewer animals, 1.86 more animals). Our integrated community modeling framework has the potential to expand the scope of inference over space, time, and levels of biological organization, but practitioners should carefully evaluate whether model assumptions are met in their systems and whether data integration is valuable for their applications.

CometChip enables parallel analysis of multiple DNA repair activities [DNA repair 106 (2021) 103176–103202] - Jing Ge; Le P. Ngo; Simran Kaushal; Ian J. Tay; Elina Thadhani; Jennifer E. Kay; Patrizia Mazzucato; Danielle Chow; Jessica Fessler; David M. Weingeist; Robert W. Sobol; Leona D. Samson; et al. (DNA Repair, 2024)

The comprehensive evaluation of nitrate origin and transformation pathways in the oxic alluvial aquifer in Serbia - Marija Perović; Vesna Obradović; Vesna Zuber-Radenković; Kay Knoeller; David Mitrinović; Zoran Čepić (Environmental Science and Pollution Research, 2024)

Ambient air particulate total lung deposited surface area (LDSA) levels in urban Europe - Xiansheng Liu; Hadiatullah Hadiatullah; Xun Zhang; Pedro Trechera; Marjan Savadkoohi; Meritxell Garcia-Marlès; Cristina Reche; Noemí Pérez; David C.S. Beddows; Imre Salma; Wanda Thén; Panayiotis Kalkavouras; et al. (Science of The Total Environment, 2023)

Peatland gully restoration with stone and timber dams (Kinder Plateau, UK) - Tim Howson; Martin Evans; Tim Allott; Emma Shuttleworth; Adam Johnston; Joe Rees; David Milledge; Donald Edokpa; Chris Lockyer; Martin Kay; Tom Spencer; David Brown; et al. (Ecological Engineering, 2023)

Genomic evidence for three distinct species in the Erebia manto complex in Central Europe (Lepidoptera, Nymphalidae) - Amanda Jospin; Yannick Chittaro; Daniel Bolt; David Demergès; Kevin Gurcel; Jürgen Hensle; Andreas Sanchez; Christophe Praz; Kay Lucek (Conservation Genetics, 2023)
A problem to implement conservation strategies is that in many cases recognized taxa are in fact complexes of several cryptic species. Failure to properly delineate species may lead to misplaced priorities or to inadequate conservation measures. One such species complex is the yellow-spotted ringlet Erebia manto , which comprises several phenotypically distinct lineages, whose degree of genomic isolation has so far not been assessed. Some of these lineages are geographically restricted and thus possibly represent distinct units with conservation priorities. Using several thousand nuclear genomic markers, we evaluated to which degree the bubastis lineage from the Alps and the vogesiaca lineage from the Vosges, are genetically isolated from the widespread manto lineage. Our results suggest that both lineages are genetically as strongly differentiated from manto as other taxonomically well separated sibling species in this genus from each other, supporting a delineation of bubastis and vogesiaca as independent species. Given the restricted and isolated range of vogesiaca as well as the disjunct distribution of bubastis, our findings have significant implication for future conservation efforts on these formerly cryptic species and highlight the need to investigate the genomic identity within species complexes.

A Near Four-Decade Time Series Shows the Hawaiian Islands Have Been Browning Since the 1980s - Austin Madson; Monica Dimson; Lucas Berio Fortini; Kapua Kawelo; Tamara Ticktin; Matt Keir; Chunyu Dong; Zhimin Ma; David W. Beilman; Kelly Kay; Jonathan Pando Ocón; Erica Gallerani; et al. (Environmental Management, 2023)
The Hawaiian Islands have been identified as a global biodiversity hotspot. We examine the Normalized Difference Vegetation Index (NDVI) using Climate Data Records products (0.05 × 0.05°) to identify significant differences in NDVI between neutral El Niño-Southern Oscillation years (1984, 2019) and significant long-term changes over the entire time series (1982–2019) for the Hawaiian Islands and six land cover classes. Overall, there has been a significant decline in NDVI (i.e., browning) across the Hawaiian Islands from 1982 to 2019 with the islands of Lāna’i and Hawai’i experiencing the greatest decreases in NDVI (≥44%). All land cover classes significantly decreased in NDVI for most months, especially during the wet season month of March. Native vegetation cover across all islands also experienced significant declines in NDVI, with the leeward, southwestern side of the island of Hawai’i experiencing the greatest declines. The long-term trends in the annual total precipitation and annual mean Palmer Drought Severity Index (PDSI) for 1982–2019 on the Hawaiian Islands show significant concurrent declines. Primarily positive correlations between the native ecosystem NDVI and precipitation imply that significant decreases in precipitation may exacerbate the decrease in NDVI of native ecosystems. NDVI-PDSI correlations were primarily negative on the windward side of the islands and positive on the leeward sides, suggesting a higher sensitivity to drought for leeward native ecosystems. Multi-decadal time series and spatially explicit data for native landscapes provide natural resource managers with long-term trends and monthly changes associated with vegetation health and stability.

EGR3 regulates opioid-related nociception and motivation in male rats - Swarup Mitra; Shruthi A. Thomas; Jennifer A. Martin; Jamal Williams; Kristen Woodhouse; Ramesh Chandra; Jun Xu Li; Mary Kay Lobo; Fraser J. Sim; David M. Dietz (Psychopharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Effects of a physical activity intervention on brain atrophy in older adults at risk of dementia: a randomized controlled trial - Benjamin Sinclair; Chris Steward; Vijay Venkatraman; Rowa Aljondi; Kay L. Cox; Kathryn A. Ellis; David Ames; Colin L. Masters; Pramit M. Phal; Matthew J. Sharman; Elizabeth V. Cyarto; Michelle M. Y. Lai; et al. (Brain Imaging and Behavior, 2021)

Plastic Pollution and Small Juvenile Marine Turtles: A Potential Evolutionary Trap - Emily M. Duncan; Annette C. Broderick; Kay Critchell; Tamara S. Galloway; Mark Hamann; Colin J. Limpus; Penelope K. Lindeque; David Santillo; Anton D. Tucker; Scott Whiting; Erina J. Young; Brendan J. Godley (Frontiers in Marine Science, 2021)
The ingestion of plastic by marine turtles is now reported for all species. Small juvenile turtles (including post-hatchling and oceanic juveniles) are thought to be most at risk, due to feeding preferences and overlap with areas of high plastic abundance. Their remote and dispersed life stage, however, results in limited access and assessments. Here, stranded and bycaught specimens from Queensland Australia, Pacific Ocean (PO; n = 65; 1993–2019) and Western Australia, Indian Ocean (IO; n = 56; 2015–2019) provide a unique opportunity to assess the extent of plastic (> 1mm) ingestion in five species [green ( Chelonia mydas ), loggerhead ( Caretta caretta ), hawksbill ( Eretmochelys imbricata ), olive ridley ( Lepidochelys olivacea ), and flatback turtles ( Natator depressus )]. In the Pacific Ocean, high incidence of ingestion occurred in green (83%; n = 36), loggerhead (86%; n = 7), flatback (80%; n = 10) and olive ridley turtles (29%; n = 7). There was an overall lower incidence in IO; highest being in the flatback (28%; n = 18), the loggerhead (21%; n = 14) and green (9%; n = 22). No macroplastic debris ingestion was documented for hawksbill turtles in either site although sample sizes were smaller for this species (PO n = 5; IO n = 2). In the Pacific Ocean, the majority of ingested debris was made up of hard fragments (mean of all species 52%; species averages 46–97%), whereas for the Indian Ocean these were filamentous plastics (52%; 43–77%). The most abundant colour for both sites across all species was clear (PO: 36%; IO: 39%), followed by white for PO (36%) then green and blue for IO (16%; 16%). The polymers most commonly ingested by turtles in both oceans were polyethylene (PE; PO-58%; IO-39%) and polypropylene (PP; PO-20.2%; IO-23.5%). We frame the high occurrence of ingested plastic present in this marine turtle life stage as a potential evolutionary trap as they undertake their development in what are now some of the most polluted areas of the global oceans.

Response to the Letter to the Editor from Costa do Couto et al. regarding our article ‘Isokinetic eccentric exercise substantially improves mobility, muscle strength and size, but not postural sway metrics in older adults with limited regression observed following a detraining period’ - Anthony David Kay; Anthony John Blazevich; Millie Fraser; Lucy Ashmore; Mathew William Hill (European Journal of Applied Physiology, 2021)

Correction to: Will I have to move because of climate change? Perceived likelihood of weather- or climate-related relocation among the US public - Byungdoo Kim; David L. Kay; Jonathon P. Schuldt (Climatic Change, 2021)

Will I have to move because of climate change? Perceived likelihood of weather- or climate-related relocation among the US public - Byungdoo Kim; David L. Kay; Jonathon P. Schuldt (Climatic Change, 2021)

Mechanisms underlying performance impairments following prolonged static stretching without a comprehensive warm-up - David G. Behm; Anthony D. Kay; Gabriel S. Trajano; Anthony J. Blazevich (European Journal of Applied Physiology, 2021)

Integrating distance sampling and presence‐only data to estimate species abundance - Matthew T. Farr; David S. Green; Kay E. Holekamp; Elise F. Zipkin (Ecology, 2021)
Integrated models combine multiple data types within a unified analysis to estimate species abundance and covariate effects. By sharing biological parameters, integrated models improve the accuracy and precision of estimates compared to separate analyses of individual data sets. We developed an integrated point process model to combine presence‐only and distance sampling data for estimation of spatially explicit abundance patterns. Simulations across a range of parameter values demonstrate that our model can recover estimates of biological covariates, but parameter accuracy and precision varied with the quantity of each data type. We applied our model to a case study of black‐backed jackals in the Masai Mara National Reserve, Kenya, to examine effects of spatially varying covariates on jackal abundance patterns. The model revealed that jackals were positively affected by anthropogenic disturbance on the landscape, with highest abundance estimated along the Reserve border near human activity. We found minimal effects of landscape cover, lion density, and distance to water source, suggesting that human use of the Reserve may be the biggest driver of jackal abundance patterns. Our integrated model expands the scope of ecological inference by taking advantage of widely available presence‐only data, while simultaneously leveraging richer, but typically limited, distance sampling data.

Isokinetic eccentric exercise substantially improves mobility, muscle strength and size, but not postural sway metrics in older adults, with limited regression observed following a detraining period - Anthony David Kay; Anthony John Blazevich; Millie Fraser; Lucy Ashmore; Mathew William Hill (European Journal of Applied Physiology, 2020)
Introduction Eccentric exercise can reverse age-related decreases in muscle strength and mass; however, no data exist describing its effects on postural sway. As the ankle may be more important for postural sway than hip and knee joints, and with older adults prone to periods of inactivity, the effects of two 6-week seated isokinetic eccentric exercise programmes, and an 8-week detraining period, were examined in 27 older adults (67.1 ± 6.0 years). Methods Neuromuscular parameters were measured before and after training and detraining periods with subjects assigned to ECC (twice-weekly eccentric-only hip and knee extensor contractions) or ECC PF (identical training with additional eccentric-only plantarflexor contractions) training programmes. Results Significant ( P < 0.05) increases in mobility (decreased timed-up-and-go time [− 7.7 to − 12.0%]), eccentric strength (39.4–58.8%) and vastus lateralis thickness (9.8–9.9%) occurred after both training programmes, with low-to-moderate weekly rate of perceived exertion (3.3–4.5/10) reported. No significant change in any postural sway metric occurred after either training programme. After 8 weeks of detraining, mobility (− 8.2 to − 11.3%), eccentric strength (30.5–50.4%) and vastus lateralis thickness (6.1–7.1%) remained significantly greater than baseline in both groups. Conclusion Despite improvements in functional mobility, muscle strength and size, lower-limb eccentric training targeting hip, knee and ankle extensor muscle groups was not sufficient to influence static balance. Nonetheless, as the beneficial functional and structural adaptations were largely maintained through an 8-week detraining period, these findings have important implications for clinical exercise prescription as the exercise modality, low perceived training intensity, and adaptive profile are well suited to the needs of older adults.

Improved clouds over Southern Ocean amplify Antarctic precipitation response to ozone depletion in an earth system model - David P. Schneider; Jennifer E. Kay; Jan Lenaerts (Climate Dynamics, 2020)

A genome-wide association study implicates the BMP7 locus as a risk factor for nonsyndromic metopic craniosynostosis - Cristina M. Justice; Araceli Cuellar; Krithi Bala; Jeremy A. Sabourin; Michael L. Cunningham; Karen Crawford; Julie M. Phipps; Yan Zhou; Deirdre Cilliers; Jo C. Byren; David Johnson; Steven A. Wall; et al. (Human Genetics, 2020)

Fruit Selectivity in Anthropoid Primates: Size Matters - Kim Valenta; David J. Daegling; Omer Nevo; Justin Ledogar; Dipto Sarkar; Urs Kalbitzer; Sarah Bortolamiol; Patrick Omeja; Colin A. Chapman; Manfred Ayasse; Richard Kay; Blythe Williams (International Journal of Primatology, 2020)

Implementation of access and benefit-sharing measures has consequences for classical biological control of weeds - Luciana Silvestri; Alejandro Sosa; Fernando Mc Kay; Marcelo Diniz Vitorino; Martin Hill; Costas Zachariades; Stephen Hight; Philip Weyl; David Smith; Djamila Djeddour; Peter G. Mason (BioControl, 2020)
The Convention on Biological Diversity and the Nagoya Protocol establish that genetic resources shall be accessed only upon the existence of prior informed consent of the country that provides those resources and that benefits arising from their utilization shall be shared. Pursuant to both agreements several countries have adopted regulations on access and benefit-sharing. These regulations have created a challenging obstacle to classical biological control of weeds. This paper reviews the experiences of Argentina, Brazil, South Africa, the USA, Canada and CABI in implementing access and benefit-sharing regulations and the implications these measures have on the effective and efficient access, exchange and utilization of biological control agents. We conclude that policy makers should be made aware of the key role biological control plays for agriculture and the environment and they are encouraged to develop tailored access and benefit-sharing legal frameworks that facilitate biological control research and implementation.

Artificial intelligence supported patient self-care in chronic heart failure: a paradigm shift from reactive to predictive, preventive and personalised care - Matthew Barrett; Josiane Boyne; Julia Brandts; Hans-Peter Brunner-La Rocca; Lieven De Maesschalck; Kurt De Wit; Lana Dixon; Casper Eurlings; Donna Fitzsimons; Olga Golubnitschaja; Arjan Hageman; Frank Heemskerk; et al. (EPMA Journal, 2019)
Heart failure (HF) is one of the most complex chronic disorders with high prevalence, mainly due to the ageing population and better treatment of underlying diseases. Prevalence will continue to rise and is estimated to reach 3% of the population in Western countries by 2025. It is the most important cause of hospitalisation in subjects aged 65 years or more, resulting in high costs and major social impact. The current “one-size-fits-all” approach in the treatment of HF does not result in best outcome for all patients. These facts are an imminent threat to good quality management of patients with HF. An unorthodox approach from a new vision on care is required. We propose a novel predictive, preventive and personalised medicine approach where patients are truly leading their management, supported by an easily accessible online application that takes advantage of artificial intelligence. This strategy paper describes the needs in HF care, the needed paradigm shift and the elements that are required to achieve this shift. Through the inspiring collaboration of clinical and high-tech partners from North-West Europe combining state of the art HF care, artificial intelligence, serious gaming and patient coaching, a virtual doctor is being created. The results are expected to advance and personalise self-care, where standard care tasks are performed by the patients themselves, in principle without involvement of healthcare professionals, the latter being able to focus on complex conditions. This new vision on care will significantly reduce costs per patient while improving outcomes to enable long-term sustainability of top-level HF care.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Biochemical diversity of glycosphingolipid biosynthesis as a driver of Coccolithovirus competitive ecology - Jozef I. Nissimov; David Talmy; Liti Haramaty; Helen F. Fredricks; Ehud Zelzion; Ben Knowles; A. Murat Eren; Rebecca Vandzura; Christien P. Laber; Brittany M. Schieler; Christopher T. Johns; Kuldeep D. More; et al. (Environmental Microbiology, 2019)
Summary Coccolithoviruses (EhVs) are large, double‐stranded DNA‐containing viruses that infect the single‐celled, marine coccolithophore Emiliania huxleyi . Given the cosmopolitan nature and global importance of E. huxleyi as a bloom‐forming, calcifying, photoautotroph, E. huxleyi –EhV interactions play a key role in oceanic carbon biogeochemistry. Virally‐encoded glycosphingolipids (vGSLs) are virulence factors that are produced by the activity of virus‐encoded serine palmitoyltransferase (SPT). Here, we characterize the dynamics, diversity and catalytic production of vGSLs in an array of EhV strains in relation to their SPT sequence composition and explore the hypothesis that they are a determinant of infectivity and host demise. vGSL production and diversity was positively correlated with increased virulence, virus replication rate and lytic infection dynamics in laboratory experiments, but they do not explain the success of less‐virulent EhVs in natural EhV communities. The majority of EhV‐derived SPT amplicon sequences associated with infected cells in the North Atlantic derived from slower infecting, less virulent EhVs. Our lab‐, field‐ and mathematical model‐based data and simulations support ecological scenarios whereby slow‐infecting, less‐virulent EhVs successfully compete in North Atlantic populations of E. huxleyi , through either the preferential removal of fast‐infecting, virulent EhVs during active infection or by having access to a broader host range.

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Trapping of lead (Pb) by corn and pea root border cells - David A. Huskey; Gilberto Curlango-Rivera; Robert A. Root; Fushi Wen; Mary Kay Amistadi; Jon Chorover; Martha C. Hawes (Plant and Soil, 2018)

Local Government Capacity to Respond to Environmental Change: Insights from Towns in New York State - Lincoln R. Larson; T. Bruce Lauber; David L. Kay; Bethany B. Cutts (Environmental Management, 2017)

The Impact of the Extreme Amazonian Flood Season on the Incidence of Viral Gastroenteritis Cases - Carmen Baur Vieira; Adriana de Abreu Corrêa; Michele Silva de Jesus; Sérgio Luiz Bessa Luz; Peter Wyn-Jones; David Kay; Mônica Simões Rocha; Marize Pereira Miagostovich (Food and Environmental Virology, 2017)

Cerebello-cerebral connectivity in the developing brain - Kay Pieterman; Dafnis Batalle; Jeroen Dudink; J-Donald Tournier; Emer J. Hughes; Madeleine Barnett; Manon J. Benders; A. David Edwards; Freek E. Hoebeek; Serena J. Counsell (Brain Structure and Function, 2017)

Effects of past and present livestock grazing on herpetofauna in a landscape‐scale experiment - Geoffrey M. Kay; Alessio Mortelliti; Ayesha Tulloch; Philip Barton; Daniel Florance; Saul A. Cunningham; David B. Lindenmayer (Conservation Biology, 2017)
Livestock grazing is the most widespread land use on Earth and can have negative effects on biodiversity. Yet, many of the mechanisms by which grazing leads to changes in biodiversity remain unresolved. One reason is that conventional grazing studies often target broad treatments rather than specific parameters of grazing (e.g., intensity, duration, and frequency) or fail to account for historical grazing effects. We conducted a landscape‐scale replicated grazing experiment (15,000 km 2 , 97 sites) to examine the impact of past grazing management and current grazing regimes (intensity, duration, and frequency) on a community of ground‐dwelling herpetofauna (39 species). We analyzed community variables (species richness and composition) for all species and built multiseason patch‐occupancy models to predict local colonization and extinction for the 7 most abundant species. Past grazing practices did not influence community richness but did affect community composition and patch colonization and extinction for 4 of 7 species. Present grazing parameters did not influence community richness or composition, but 6 of the 7 target species were affected by at least one grazing parameter. Grazing frequency had the most consistent influence, positively affecting 3 of 7 species (increased colonization or decreased extinction). Past grazing practice affected community composition and population dynamics in some species in different ways, which suggests that conservation planners should examine the different grazing histories of an area. Species responded differently to specific current grazing practices; thus, incentive programs that apply a diversity of approaches rather than focusing on a change such as reduced grazing intensity should be considered. Based on our findings, we suggest that determining fine‐scale grazing attributes is essential for advancing grazing as a conservation strategy.

By their own devices: invasive Argentine ants have shifted diet without clear aid from symbiotic microbes - Yi Hu; David A. Holway; Piotr Łukasik; Linh Chau; Adam D. Kay; Edward G. LeBrun; Katie A. Miller; Jon G. Sanders; Andrew V. Suarez; Jacob A. Russell (Molecular Ecology, 2017)
The functions and compositions of symbiotic bacterial communities often correlate with host ecology. Yet cause–effect relationships and the order of symbiont vs. host change remain unclear in the face of ancient symbioses and conserved host ecology. Several groups of ants exemplify this challenge, as their low‐nitrogen diets and specialized symbioses appear conserved and ancient. To address whether nitrogen‐provisioning symbionts might be important in the early stages of ant trophic shifts, we studied bacteria from the Argentine ant, Linepithema humile – an invasive species that has transitioned towards greater consumption of sugar‐rich, nitrogen‐poor foods in parts of its introduced range. Bacteria were present at low densities in most L. humile workers, and among those yielding quality 16S rRNA amplicon sequencing data, we found just three symbionts to be common and dominant. Two, a Lactobacillus and an Acetobacteraceae species, were shared between native and introduced populations. The other, a Rickettsia , was found only in two introduced supercolonies. Across an eight‐year period of trophic reduction in one introduced population, we found no change in symbionts, arguing against a relationship between natural dietary change and microbiome composition. Overall, our findings thus argue against major changes in symbiotic bacteria in association with the invasion and trophic shift of L. humile . In addition, genome content from close relatives of the identified symbionts suggests that just one can synthesize most essential amino acids; this bacterium was only modestly abundant in introduced populations, providing little support for a major role of nitrogen‐provisioning symbioses in Argentine ant's dietary shift.

Genomic landscape of early ecological speciation initiated by selection on nuptial colour - David Alexander Marques; Kay Lucek; Marcel Philipp Haesler; Anna Fiona Feller; Joana Isabel Meier; Catherine E. Wagner; Laurent Excoffier; Ole Seehausen (Molecular Ecology, 2017)
Ecological speciation is the evolution of reproductive isolation as a consequence of direct divergent natural selection or ecologically mediated divergent sexual selection. While the genomic signature of the former has been extensively studied in recent years, only few examples exist for genomic differentiation where environment‐dependent sexual selection has played an important role. Here, we describe a very young (~90 years old) population of threespine sticklebacks exhibiting phenotypic and genomic differentiation between two habitats within the same pond. We show that differentiation among habitats is limited to male throat colour and nest type, traits known to be subject to sexual selection. Divergence in these traits mirrors divergence in much older benthic and limnetic stickleback species pairs from North American west coast lakes, which also occur in sympatry but are strongly reproductively isolated from each other. We demonstrate that in our population, differences in throat colour and breeding have been stable over a decade, but in contrast to North American benthic and limnetic stickleback species, these mating trait differences are not accompanied by divergence in morphology related to feeding, predator defence or swimming performance. Using genomewide SNP data, we find multiple genomic islands with moderate differentiation spread across several chromosomes, whereas the rest of the genome is undifferentiated. The islands contain potential candidate genes involved in visual perception of colour. Our results suggest that phenotypic and multichromosome genomic divergence of these morphs was driven by environment‐dependent sexual selection, demonstrating incipient speciation after only a few decades of divergence in sympatry.

Using empirical models of species colonization under multiple threatening processes to identify complementary threat‐mitigation strategies - Ayesha I.T. Tulloch; Alessio Mortelliti; Geoffrey M. Kay; Daniel Florance; David Lindenmayer (Conservation Biology, 2016)
Approaches to prioritize conservation actions are gaining popularity. However, limited empirical evidence exists on which species might benefit most from threat mitigation and on what combination of threats, if mitigated simultaneously, would result in the best outcomes for biodiversity. We devised a way to prioritize threat mitigation at a regional scale with empirical evidence based on predicted changes to population dynamics—information that is lacking in most threat‐management prioritization frameworks that rely on expert elicitation. We used dynamic occupancy models to investigate the effects of multiple threats (tree cover, grazing, and presence of an hyperaggressive competitor, the Noisy Miner (Manorina melanocephala) on bird‐population dynamics in an endangered woodland community in southeastern Australia. The 3 threatening processes had different effects on different species. We used predicted patch‐colonization probabilities to estimate the benefit to each species of removing one or more threats. We then determined the complementary set of threat‐mitigation strategies that maximized colonization of all species while ensuring that redundant actions with little benefit were avoided. The single action that resulted in the highest colonization was increasing tree cover, which increased patch colonization by 5% and 11% on average across all species and for declining species, respectively. Combining Noisy Miner control with increasing tree cover increased species colonization by 10% and 19% on average for all species and for declining species respectively, and was a higher priority than changing grazing regimes. Guidance for prioritizing threat mitigation is critical in the face of cumulative threatening processes. By incorporating population dynamics in prioritization of threat management, our approach helps ensure funding is not wasted on ineffective management programs that target the wrong threats or species.

Viruses Surveillance Under Different Season Scenarios of the Negro River Basin, Amazonia, Brazil - Carmen Baur Vieira; Adriana de Abreu Corrêa; Michele Silva de Jesus; Sérgio Luiz Bessa Luz; Peter Wyn-Jones; David Kay; Marta Vargha; Marize Pereira Miagostovich (Food and Environmental Virology, 2016)

Molecular tools for bathing water assessment in Europe: Balancing social science research with a rapidly developing environmental science evidence-base - David M. Oliver; Nick D. Hanley; Melanie van Niekerk; David Kay; A. Louise Heathwaite; Sharyl J. M. Rabinovici; Julie L. Kinzelman; Lora E. Fleming; Jonathan Porter; Sabina Shaikh; Rob Fish; Sue Chilton; et al. (Ambio, 2016)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

The novel mu-opioid antagonist, GSK1521498, reduces ethanol consumption in C57BL/6J mice - Tamzin L. Ripley; Sandra Sanchez-Roige; Edward T. Bullmore; Manolo Mugnaini; Kay Maltby; Sam R. Miller; David R. Wille; Pradeep Nathan; David N. Stephens (Psychopharmacology, 2015)

Diversity of acidophilic prokaryotes at two acid mine drainage sites in Turkey - Pınar Aytar; Catherine Melanie Kay; Mehmet Burçin Mutlu; Ahmet Çabuk; David Barrie Johnson (Environmental Science and Pollution Research, 2015)

Recreational Water and Infection: A Review of Recent Findings - Lorna Fewtrell; David Kay (Current Environmental Health Reports, 2015)

A Simplified Approach for Simultaneous Measurements of Wavefront Velocity and Curvature in the Heart Using Activation Times - Nachaat Mazeh; David E. Haines; Matthew W. Kay; Bradley J. Roth (Cardiovascular Engineering and Technology, 2013)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Profiling drug-induced cell death pathways in the zebrafish lateral line - Allison B. Coffin; Kay L. Williamson; Anna Mamiya; David W. Raible; Edwin W. Rubel (Apoptosis, 2013)

Use of a physiologically-based pharmacokinetic model to simulate artemether dose adjustment for overcoming the drug-drug interaction with efavirenz - Marco Siccardi; Adeniyi Olagunju; Kay Seden; Farid Ebrahimjee; Steve Rannard; David Back; Andrew Owen (In Silico Pharmacology, 2013)
Purpose To treat malaria, HIV-infected patients normally receive artemether (80 mg twice daily) concurrently with antiretroviral therapy and drug-drug interactions can potentially occur. Artemether is a substrate of CYP3A4 and CYP2B6, antiretrovirals such as efavirenz induce these enzymes and have the potential to reduce artemether pharmacokinetic exposure. The aim of this study was to develop an in vitro in vivo extrapolation (IVIVE) approach to model the interaction between efavirenz and artemether. Artemether dose adjustments were then simulated in order to predict optimal dosing in co-infected patients and inform future interaction study design. Methods In vitro data describing the chemical properties, absorption, distribution, metabolism and elimination of efavirenz and artemether were obtained from published literature and included in a physiologically based pharmacokinetic model (PBPK) to predict drug disposition simulating virtual clinical trials. Administration of efavirenz and artemether, alone or in combination, were simulated to mirror previous clinical studies and facilitate validation of the model and realistic interpretation of the simulation. Efavirenz (600 mg once daily) was administered to 50 virtual subjects for 14 days. This was followed by concomitant administration of artemether (80 mg eight hourly) for the first two doses and 80 mg (twice daily) for another two days. Results Simulated pharmacokinetics and the drug-drug interaction were in concordance with available clinical data. Efavirenz induced first pass metabolism and hepatic clearance, reducing artemether C max by 60% and AUC by 80%. Dose increases of artemether, to correct for the interaction, were simulated and a dose of 240 mg was predicted to be sufficient to overcome the interaction and allow therapeutic plasma concentrations of artemether. Conclusions The model presented here provides a rational platform to inform the design for a clinical drug interaction study that may save time and resource while the optimal dose is determined empirically. Wider application of IVIVE could help researchers gain a better understanding of the molecular mechanisms underpinning variability in drug disposition.

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Intracellular-signaling tumor-regression modeling of the pro-apoptotic receptor agonists dulanermin and conatumumab - Brittany P. Kay; Cheng-Pang Hsu; Jian-Feng Lu; Yu-Nien Sun; Shuang Bai; Yan Xin; David Z. D’Argenio (Journal of Pharmacokinetics and Pharmacodynamics, 2012)

Cues, Not an Endogenous Rhythm, Control the Dusk Peak in Water-Column Entry by Benthic Copepods - Kay Vopel; David Thistle (Estuaries and Coasts, 2011)

Reaching Further with Online Education? The Development of an Effective Online Program in Palliative Oncology - Bogda Koczwara; Kay Francis; Franca Marine; David Goldstein; Craig Underhill; Ian Olver (Journal of Cancer Education, 2010)

Natural enemies of balloon vine Cardiospermum grandiflorum (Sapindaceae) in Argentina and their potential use as biological control agents in South Africa - Fernando Mc Kay; Marina Oleiro; Andries Fourie; David Simelane (International Journal of Tropical Insect Science, 2010)

An Early Pliocene lake and its surrounding vegetation in Zhejiang, East China - Jin-Feng Li; Ya-Qin Hu; David Kay Ferguson; Yu-Fei Wang; Cheng-Sen Li (Journal of Paleolimnology, 2010)

Nutrition and interference competition have interactive effects on the behavior and performance of Argentine ants - Adam D. Kay; Taylor Zumbusch; Justa L. Heinen; Tom C. Marsh; David A. Holway (Ecology, 2010)
Food availability often influences competitive outcomes through effects on consumer growth. Although it has received less attention, food availability may also affect competition through nutritional effects on behavior. One hypothesis linking nutrition and competition in ants posits that increased access to carbohydrates favors greater investment in worker traits that underlie behavioral dominance. We tested this hypothesis by varying dietary protein : carbohydrate (P:C) ratios and levels of interspecific interference for Argentine ants ( Linepithema humile ), a widespread invasive species. As predicted, colonies facing interference increased patrolling more when reared on low P:C diets; this result is the first demonstration of an interactive effect of nutrition and interference on ant colonies. Several results suggest that this dietary effect on patrolling was due primarily to changes in colony size rather than worker behavior. Colonies on lower P:C diets had lower worker mortality and larger final colony sizes. Diet had little effect on per capita patrolling, and worker behavior in performance assays depended more on previous exposure to interference than on diet. Our findings indicate that dietary P:C ratios can influence Argentine ant performance in a competitive environment and suggest a mechanism by which monopolization of carbohydrate‐rich resources can help invasive ants displace native ant competitors.

Hydro-epidemiology: the emergence of a research agenda - David Kay; Roger Falconer (Environmental Fluid Mechanics, 2008)

Contrasting levels of genetic differentiation among putative neutral microsatellite loci in Atlantic herring Clupea harengus populations and the implications for assessing stock structure - Phillip C. Watts; David O’Leary; Mary C. Cross; Jamie Coughlan; Eileen Dillane; Suzanne M. Kay; Suzanne Wylde; René Stet; Richard D. M. Nash; Emma M. C. Hatfield; Thomas F. Cross (Hydrobiologia, 2008)

New observations on Micropleura australiensis (Nematoda, Dracunculoidea), a parasite of crocodiles in Australia - František Moravec; David Spratt; Winston Kay (Acta Parasitologica, 2007)

New observations on Micropleura australiensis (Nematoda, Dracunculoidea), a parasite of crocodiles in Australia - František Moravec; David Spratt; Winston Kay (Acta Parasitologica, 2006)
Scanning electron microscopy examination of male and female specimens of Micropleura australiensis Moravec, Kay et Hobbs, 2004 (Nematoda, Dracunculoidea) from the peritoneal cavity of the freshwater crocodile Crocodylus johnsoni of the Ord River in Western Australia revealed some previously unreported morphological features. The male, first studied by SEM, possesses the same number (14) of cephalic papillae as the gravid female, but these are comparatively larger and somewhat differently arranged; four slit-like depressions located near the inner base of male dorsolateral and ventrolateral cephalic papillae of the external circle are present. The inner margin of the female oral aperture is smooth, without papilla-like formations. The male caudal end is provided with a right-side ventral ala. The transverse cuticular striae on the male ventral surface bear minute ornamentations (rows of papilla-like formations) in the pre-and postcloacal region. For the first time, M. australiensis is reported from wild and farmed Crocodylus johnsoni and saltwater crocodile C. porosus (new host record) from four localities in the Northern Territory, Australia.

Root response to Fusarium solani f. sp . glycines: temporal accumulation of transcripts in partially resistant and susceptible soybean - M. J. Iqbal; Satsuki Yaegashi; Rubina Ahsan; Kay L. Shopinski; David A. Lightfoot (Theoretical and Applied Genetics, 2005)

Towards a mutant map of the mouse ? new models of neurological, behavioural, deafness, bone, renal and blood disorders - Sohaila Rastan; Tertius Hough; Amy Kierman; Rachel Hardisty; Alexandra Erven; Ian C. Gray; Stepanie Voeling; Adrian Isaacs; Hsun Tsai; Mark Strivens; Rebecca Washbourne; Claire Thornton; et al. (Genetica, 2004)

Do Harpacticoids (Copepoda) Use Water‐Borne Cues to Aid in Locating Food Parcels? - Andrea Fechter; David Thistle; Günter Arlt; Keith Suderman; Kay Vopel (Marine Ecology, 2004)
Harpacticoid copepod food is patchily distributed and individuals must episodically move to new food patches. Key questions in harpacticoid feeding ecology include how individuals detect food patches and how rapidly they move toward patches. Based on literature reports, we hypothesized that harpacticoids locate food parcels by sensing a water‐borne cue. We tested this idea using individuals of Leptastacus coulli Huys, 1992 and Praeleptomesochra similis Lang, 1965 from a sandy beach in north Florida (29.948° N, 84.341° W). Individuals from both species selected seawater that had been exposed to food significantly more frequently than they selected control seawater. The rate of movement of these species was millimeters per second, which agreed with previous reports.

Extracting Wave Structure from Biological Data with Application to Responses in Turtle Visual Cortex - Kay A. Robbins; David M. Senseman (Journal of Computational Neuroscience, 2004)

The timing of benthic copepod emergence - Michael Teasdale; Kay Vopel; David Thistle (Limnology and Oceanography, 2004)
We investigated emergence of marine benthic harpacticoid and cyclopoid copepods from subtidal sediment into the bottom water. Previous studies that used traps in the field found that copepods emerged from the sediment within 2 h of dusk. We examined emergence in 20‐min sampling periods over 13 h from 1200 to 0100 h in a laboratory flume under conditions of constant flow speed. The light intensity was adjusted to field conditions every 20 min. We observed a peak in emergence during the 20‐min sampling period after the onset of darkness, greatly increasing the accuracy with which the timing of emergence is known. This result will help to set the stage for studies of emergence cues.

Effect of the brittle star Amphiura filiformis (Amphiuridae, Echinodermata) on oxygen flux into the sediment - Kay Vopel; David Thistle; Rutger Rosenberg (Limnology and Oceanography, 2003)
O 2 plays a key role in early sedimentary diagenetic processes, but the effect of most macrofaunal species on the pathways and rates of supply of O 2 into the seabed are not well known. We investigated the effect of the ophiuroid Amphiura filiformis , one of the dominant macrobenthic species on soft bottoms in the northeast Atlantic, at depths of ~15–100 m, in a laboratory environment. We determined how the presence of the ophiuroid changed the total O 2 uptake of macrofauna‐free sediment by combining measurements from a microcosm approach and an approach that uses microelectrodes and a flushed aquarium. We suggest that natural populations of A. filiformis can account for 80% of the total flux of O 2 into the soft bottom. At least 67% of this portion is due to the diffusion of O 2 across additional sediment‐water interfaces excavated by the brittle star.

The importance of alcohol-induced muscle disease - Victor R. Preedy; Kay Ohlendieck; Junko Adachi; Michael Koll; Alan Sneddon; Ross Hunter; Rajkumar Rajendram; David Mantle; Timothy J. Peters (Journal of Muscle Research and Cell Motility, 2003)

A comprehensive worksite cancer prevention intervention: behavior change results from a randomized controlled trial (United States) - Glorian Sorensen; Anne M Stoddard; Anthony D. LaMontagne; Karen Emmons; Mary Kay Hunt; Richard Youngstrom; Deborah McLellan; David C Christiani (Cancer Causes & Control, 2002)

Public Support for Ecosystem Restoration in the Hudson River Valley, USA - NANCY A. CONNELLY; BARBARA A. KNUTH; DAVID L. KAY (Environmental Management, 2002)

Dissection of abscisic acid signal transduction pathways in barley aleurone layers - Qingxi Shen; Aurelio Gomez-Cadenas; Pengnian Zhang; Mary Kay Walker-Simmons; Jen Sheen; Tuan-Hua David Ho (Plant Molecular Biology, 2001)

Fibroblast Growth Factor Inhibits Expression of Neural Markers in Cultures of Zebrafish Early Embryo Cells - Natalia N. Singh; Kay Fischer; Olaf Hedstrom; David W. Barnes (Marine Biotechnology, 2001)

Population Pharmacokinetics of Fast Release Oral Diclofenac in Healthy Volunteers: Relation to Pharmacodynamics in an Experimental Pain Model - Jörn Lötsch; Birgit Kettenmann; Bertold Renner; David Drover; Kay Brune; Gerd Geisslinger; Gerd Kobal (Pharmaceutical Research, 2000)

Angiogenesis induced by tumor necrosis factor-agr; is mediated by α4 integrins - Peter Vanderslice; Christy L. Munsch; Eugene Rachal; David Erichsen; Kay M. Sughrue; Ann N. Truong; James N. Wygant; Bradley W. McIntyre; Suzanne G. Eskin; Ronald G. Tilton; Peter J. Polverini (Angiogenesis, 1998)

Functional studies on the anti-pathoangiogenic properties of CM101 - He-Ping Yan; Clint E. Carter; En-ze Wang; David L. Page; Kay Washington; Barbara D. Wamil; F. Michael Yakes; Gary B. Thurman; Carl G. Hellerqvist (Angiogenesis, 1998)

The amelioration of aluminium toxicity by silicon in wheat ( Triticum aestivum L.): malate exudation as evidence for an in planta mechanism - Kay M. Cocker; David E. Evans; Martin J. Hodson (Planta, 1998)

An epidemiological approach investigating respiratory disease response in sensitive individuals to indoor and outdoor pollen exposure in Tucson, Arizona - Mary Kay O'Rourke; James Joseph Quackenboss; Michael David Lebowitz (Aerobiologia, 1989)

Cross-reactions among carbonic anhydrases I, II, and III studied by binding tests and with monoclonal antibodies - Robert P. Erickson; Gary Kay; David Hewett-Emmett; Richard E. Tashian; J. Latham Claflin (Biochemical Genetics, 1982)